2011
DOI: 10.1111/j.1463-1318.2010.02529.x
|View full text |Cite
|
Sign up to set email alerts
|

Defunctioning stomas prior to chemoradiation for anal cancer are usually permanent

Abstract: Most patients who undergo a defunctioning stoma before CRT will not undergo subsequent reversal. The patient should therefore be informed that the stoma is likely to be permanent and this should be taken into account when considering the type and site of stoma to be formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
(28 reference statements)
0
20
1
7
Order By: Relevance
“…34 A wider indication for a pretreatment colostomy could explain this higher proportion of patients with subsequent colostomy reversal. 10,14,34 None of the patients who had a pretreatment colostomy in our study ultimately became free from colostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 A wider indication for a pretreatment colostomy could explain this higher proportion of patients with subsequent colostomy reversal. 10,14,34 None of the patients who had a pretreatment colostomy in our study ultimately became free from colostomy.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,34 None of the patients who had a pretreatment colostomy in our study ultimately became free from colostomy. 14, 34 Our study regarding cause-specific colostomy rates had some strengths and limitations. 14 In another study from the United Kingdom, seven of 35 patients had their pretreatment colostomy reversed within 6 to 30 months after curative-dose chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown than between 80 and 100% are never reversed [88,93], and, as such, patients should be warned preoperatively of the high probability that their colostomy will be permanent.…”
Section: Defunctioning Colostomy Ratesmentioning
confidence: 96%
“…Colostomy rates vary widely and have been reported to be necessary in between 4 and 34% of patients [88,[93][94][95][96]. Therapeutic colostomy may be required during or after completion of chemoradiotherapy [76] in up to a further 8% of patients due to local treatment side effects such as pain, incontinence and anal stenosis [96].…”
Section: Defunctioning Colostomy Ratesmentioning
confidence: 99%
“…Insbesondere bei radiogenen Fisteln scheint ein spontaner Verschluss durch alleinige Stomaanlage selten zu sein [222]. Eine Studie mit Patientinnen, bei denen wegen eines Analkarzinoms vor der Radiochemotherapie ein Stoma angelegt wurde, kommt zu dem Schluss, dass nach erfolgter Behandlung eine Rückverlagerung des Stomas selten ist [58]. In allen anderen Fällen muss die Indikation zur sekundären Anlage eines Stomas individuell gestellt werden.…”
Section: Stomaanlageunclassified